The sled race - Tabor, Corey R.; Webb, Dalton (New York : Greenwillow Books, an imprint of HarperCollins Publishers, 2025)
Wally Mammoth lives in the Ice Age, where his huge heart warms even the coldest of days. And it has to be cold to have a sled race! Wally and his friends Otto the great auk and Wolf the (you guessed it!) gray wolf are all hot cocoa-ed up and ready to compete. Otto and Wolf both really want to win, but sweet Wally is happy as long as everyone has fun. Naturally, the competition goes downhill quickly. If the three friends careen toward the finish line in a giant snowball, how will they determine 1st, 2nd, and 3rd place? It doesn't matter -- there will be cupcakes for everyone regardless.
Junior Library Guild
Ages 5-7.
Grades K-2.
A Junior Library Guild selection (JLG)
Keywords: Mammoth, Wally -- (Fictitious character) -- Juvenile fiction; Mammoth, Wally -- (Fictitious character) -- Fiction; Mammoth, Wally -- (Fictitious character) -- Fiction; Sledding -- Juvenile fiction; Winter -- Juvenile fiction; Sledding -- Fiction; Winter -- Fiction; Sledding -- Fiction; Winter -- Fiction